2017
DOI: 10.2196/mhealth.6496
|View full text |Cite
|
Sign up to set email alerts
|

Cloudy with a Chance of Pain: Engagement and Subsequent Attrition of Daily Data Entry in a Smartphone Pilot Study Tracking Weather, Disease Severity, and Physical Activity in Patients With Rheumatoid Arthritis

Abstract: BackgroundThe increasing ownership of smartphones provides major opportunities for epidemiological research through self-reported and passively collected data.ObjectiveThis pilot study aimed to codesign a smartphone app to assess associations between weather and joint pain in patients with rheumatoid arthritis (RA) and to study the success of daily self-reported data entry over a 60-day period and the enablers of and barriers to data collection.MethodsA patient and public involvement group (n=5) and 2 focus gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(76 citation statements)
references
References 20 publications
3
70
0
Order By: Relevance
“…In a study that required older people with rheumatoid arthritis (RA) to use smartphones to monitor their symptoms, users were highly motivated to participate because they expressed a perception that they would personally benefit alongside providing researchers with clinically relevant information (Reade et al 2017). Middlemass et al (2017) identified that older people with chronic obstructive pulmonary disease perceived an advantage of engagement with DHT through the monitoring of their health trends which enabled detection of the early onset of infections.…”
Section: Perceived Benefits Of Dht Introductionmentioning
confidence: 99%
“…In a study that required older people with rheumatoid arthritis (RA) to use smartphones to monitor their symptoms, users were highly motivated to participate because they expressed a perception that they would personally benefit alongside providing researchers with clinically relevant information (Reade et al 2017). Middlemass et al (2017) identified that older people with chronic obstructive pulmonary disease perceived an advantage of engagement with DHT through the monitoring of their health trends which enabled detection of the early onset of infections.…”
Section: Perceived Benefits Of Dht Introductionmentioning
confidence: 99%
“…Early examples of electronic pain diaries used web-based desktop interfaces [20] or personal digital assistants (PDAs) [24,41] to facilitate pain logging ( [1]) and there is now a plethora of commercial apps that allow people to monitor their pain [22,39]. Several research prototypes based on standardised scales have also been developed, with user feedback indicating positive acceptance of these applications [33]. However, most of these applications have received little or no formative evaluation in the field, with studies instead relying on preliminary user feedback and usability testing to justify their designs (e.g.…”
Section: Supporting Self-logging Of Pain With Diariesmentioning
confidence: 99%
“…However, most of these applications have received little or no formative evaluation in the field, with studies instead relying on preliminary user feedback and usability testing to justify their designs (e.g. [20,21,33]).…”
Section: Supporting Self-logging Of Pain With Diariesmentioning
confidence: 99%
See 1 more Smart Citation
“…Data-adaptive techniques (such as machine learning) combined with thoughtful human input are increasingly being used to mine electronic health record databases [34, 35] and improve analytic methods commonly used in pharmacoepidemiology [36, 37]. The ability to collect more data from mobile devices enables exploration of new issues, e.g., the relation between weather and joint pain in patients with rheumatoid arthritis [38]. Pushing the boundaries and leveraging progress made in other research areas will continue to help advance the field of pharmacoepidemiology.…”
Section: Boldermentioning
confidence: 99%